Case for diagnosis. Ulcerated intradermal nevus simulating Sister Mary Joseph's nodule - Luísa Groba Bandeira; Juliana Uchiyama; Neusa Yuriko Sakai Valente; Mário Cézar Pires (Sociedade Brasileira de Dermatologia, 2018)
Abstract: We report a case of a 76-year-old patient with a history of recent weight loss and ulcerated umbilical nodular lesion. Initially, we considered the diagnostic hypothesis of Sister Mary Joseph's nodule. However, histopathological evaluation revealed that it was an ulcerated intradermal nevus. We perform a brief review of umbilical nodules.